2021
DOI: 10.1002/nano.202000141
|View full text |Cite
|
Sign up to set email alerts
|

Nanotheranostics in epilepsy: A perspective for multimodal diagnosis and strategic management

Abstract: Epilepsy is a common but a complex neurological disorder with limited practices for successful management due to the complicated neuronal network and lack of knowledge of epileptic pathophysiology. Theranostic systems such as implantable devices and biodegradable nanomaterials offer better tailor‐made methods for the detection and treatment using nanotechnology‐based approaches for patients with epilepsy. Miniaturized nano‐implantable devices and biosensors equipped with operations to mimic neurostimulation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…In the current study, gelatin, as a smart polymer, displays a self-regulated release, in response to pH changes, while the magnetic core part of the NPs, as an externally addressable part, could be used for directing the delivery to the specific region. In the case of externally stimuli-regulated mechanisms, it has been demonstrated that microbubbles formed by ultrasound can open the tight junctions of BBB and help the medications enter CNS disorders 65 . In addition, non-invasive focused ultrasound therapy causes a reduction in the progression of epilepsy 65 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, gelatin, as a smart polymer, displays a self-regulated release, in response to pH changes, while the magnetic core part of the NPs, as an externally addressable part, could be used for directing the delivery to the specific region. In the case of externally stimuli-regulated mechanisms, it has been demonstrated that microbubbles formed by ultrasound can open the tight junctions of BBB and help the medications enter CNS disorders 65 . In addition, non-invasive focused ultrasound therapy causes a reduction in the progression of epilepsy 65 .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of externally stimuli-regulated mechanisms, it has been demonstrated that microbubbles formed by ultrasound can open the tight junctions of BBB and help the medications enter CNS disorders 65 . In addition, non-invasive focused ultrasound therapy causes a reduction in the progression of epilepsy 65 . Hence, the future direction of research in the field of smart multifunctional NPs for brain disorders with epileptic symptoms could be developing a novel technique for deeper penetration effects across the BBB (such as ultrasound-responsive neuromodulation) and facilitating the translation of the smart NPs from bench to clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that there are some concerns for human health due to the environmental problems regarding some metals, the concept of green metallic NPs has emerged and efforts have been made to produce metallic NPs with good safety profiles and low environmental impact [ 79 , 80 ]. Moreover, a highlight also goes to theragnostics, which are systems, including both applications of treatment and diagnosis [ 81 ]. An example is given by Long et al, as described later in this manuscript [ 82 ].…”
Section: Are Nanomedicines the Solution?mentioning
confidence: 99%
“…Moreover, antiseizure activity was also exhibited by the nanoformulation, confirming its use in theragnostics [ 82 ]. These agents are able to reduce the timespan for the treatment of epileptic patients, monitoring the biodistribution of the NPs in the body [ 81 ].…”
Section: Nanoparticles For Diagnosis and Theragnosticsmentioning
confidence: 99%
“…In epilepsy, the microenvironment pH at the diseased site may shift from neutral to acidic or alkaline due to factors including hypoxia, inflammation, or excess carbonic acid. 10 PHresponsive nanocarriers, such as modified hydrogels, liposomes, and other nanoparticles, are functionalized with pH-sensitive agents. These nanocarriers effectively detect changes in pH and undergo physical changes, leading to the release of drugs specifically at the diseased site without affecting normal tissue.…”
Section: Epilepsymentioning
confidence: 99%